2012
DOI: 10.4077/cjp.2012.amm107
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Probiotic Lactobacillus paracasi on Ventricles of BALB/C Mice Treated with Ovalbumin

Abstract: Lactic acid bacteria (LAB) are microorganisms that benefit animals with allergic diseases and intestinal disorders such as inflammatory bowel disease. We propose that LAB can prevent cardiomyocytes inflammation and apoptosis in BALB/c mice using an ovalbumin (OVA)-induced allergy. Thirty-nine male BALB/c mice were divided into five groups: normal control, allergy control and three allergy groups each treated with Kefir I (Kefir I), Kefir II (Kefir II) or GM080 products (GM080). The myocardial architecture and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Additionally in the same study, S. boulardii prevented the activation of caspases-9 and -8, which together led to the anti-apoptotic activities of S. boulardii against pathogens [55]. Similar results were obtained by Wang et al who reported that the probiotic mixture, kefir, reduced ovalbumin induced apoptosis in mouse heart tissues by limiting levels of the pro-apoptotic proteins Bax and Bad, cytochrome c and caspase-3 [56]. Administration of probiotic mixtures also depressed expression of apoptosis linked proteins such as pro-apoptotic Bax, caspase-3 and -8, and anti-apoptotic Bcl-2 in the livers of rats fed a methionine choline-deficient diet [57].…”
Section: Mechanisms Of Probiotic Actionsupporting
confidence: 54%
See 1 more Smart Citation
“…Additionally in the same study, S. boulardii prevented the activation of caspases-9 and -8, which together led to the anti-apoptotic activities of S. boulardii against pathogens [55]. Similar results were obtained by Wang et al who reported that the probiotic mixture, kefir, reduced ovalbumin induced apoptosis in mouse heart tissues by limiting levels of the pro-apoptotic proteins Bax and Bad, cytochrome c and caspase-3 [56]. Administration of probiotic mixtures also depressed expression of apoptosis linked proteins such as pro-apoptotic Bax, caspase-3 and -8, and anti-apoptotic Bcl-2 in the livers of rats fed a methionine choline-deficient diet [57].…”
Section: Mechanisms Of Probiotic Actionsupporting
confidence: 54%
“…In in vitro studies, Lee et al observed probiotic-induced down-regulation of the inflammatory pathway induced by LPS, including effects on NF-κB nuclear translocation, IkBa degradation and TLR4 mRNA [79]. Similarly, Wang et al recently proposed that inflammation signaling induced by ovalbumin-affected allergy could be involved in increased TLR4 and subsequent activation of phospholate-Jun- N -terminal kinase (p-JNK), JNK1/2 (p-NFkB), p-IkB and TNF-α in the hearts of allergy-prone mice [56]. In contrast, a probiotic mixture composed mainly of lactic acid bacteria reversed this inflammation by restricting inflammatory signaling pathways [56].…”
Section: Mechanisms Of Probiotic Actionmentioning
confidence: 99%
“…In fact some strains of probiotic microbes can reduce gut permeability through direct effects on intestinal epithelial cells and reduce inflammation [5, 7678]. Probiotics can mediate their beneficial activity through several mechanisms including (a) competitive exclusion of bacterial adherence and/or translocation; (b) release of bacteriocidin and lactic acid, which can inhibit the growth of pathogens; (c) production of butyric acid; (d) antioxidative effects; (e) enhancement of barrier function; (f) modulation of immune cell response; and (g) inhibition of NF- κ B activation [7987]. We will discuss several of the most prominently emerging probiotic foods and microorganisms that impact the intestinal barrier.…”
Section: Microbial Products and The Intestinal Epithelial Barriermentioning
confidence: 99%
“…In our study, we showed a similar result that three MAPKs (pERK, p-p38 and pJNK) and NF-κB signaling pathways were activated in LPSinduced DC (Figure 1). Kefir and its biological activities exerted anti-inflammatory and antioxidant effects through inhibiting p-p38 and p-NF-κB in several animal diseased model (Chen et al, 2020;Chen et al, 2019;Wang et al, 2012;Azizi et al, 2021) and exhibited antidepressant and antitumor effects through inactivation of p-ERK signaling pathway (Azizi et al, 2021;Chen et al, 2021). As anticipated, we showed a similar result as previous studies described, the levels of p-ERK and p-p38, and NF-κB/p65 nuclear translocation were significantly decreased under both doses of KPs treatment (Figure 1).…”
Section: Discussionmentioning
confidence: 99%